Cooperative Space Analysis and Simulation of Multi Manipulator - Chengwen Zou; Ping Tao (Jixie chuandong)
Monte Carlo method and envelope method are used to analyze the cooperative space and singular points of multi manipulator cooperative system model. The standard D-H parameter method is used to establish the coordinate system， the kinematics model of the robot is established in Matlab， and the forward kinematics equation of the robot is obtained. The workspace of each manipulator is obtained by Monte Carlo method， the common area points are extracted by envelope method， and the cooperation space of the multi manipulator cooperation system and the joint angle range of each manipulator in the cooperation space are obtained. An algorithm to calculate the operability is presented. According to the algorithm， the singularity distribution of multi manipulator in the cooperative space is calculated and analyzed. The Matlab/Robotics toolbox is used to build the simulation platform， and the algorithm is compiled for simulation analysis， which verifies the correctness and rationality of the kinematics model analysis of the multi robot cooperative system， the feasibility of the proposed algorithm is proved and the foundation for the subsequent coordinated operation and trajectory planning to avoid singular points is laid.